Social vulnerability among Brazilian children in early childhood: a scoping review - Alcina M. Brito; Deisiane O. Souto; Luana C. Silva; Hércules R. Leite; Rosane L.S. Morais (Jornal de Pediatria)
Objective: To identify, map, and describe studies involving Brazilian children in early childhood in situations of social vulnerability. Source of data: A scoping review including full articles published in Portuguese and English up to March 2023, with no temporal restrictions. Searches were conducted in the MEDLINE/PubMed, Scielo, EMBASE, Cochrane, Scopus, CINAHL, Web of Science, PEDro, and LILACS databases. Journal metrics, sample characteristics, study area, characterization of the situation of social vulnerability, and study outcomes were extracted. Summary of the findings: Seventy-six articles involving a total of 107.740 children in early childhood were included in this study. These studies presented relevant findings, including the temporal publication trend, the variability of social vulnerability indicators, the scarcity of intervention studies, and the fact that 100% of eligible studies were from the health area. Negative outcomes were associated with the condition of social vulnerability in almost the entire sample, reinforcing the need for government policies capable of protecting early childhood from the effects of social vulnerability. Conclusion: This scoping review mapped important findings involving Brazilian children in social vulnerability. It also identified literature gaps such as the need for intervention and multisectoral studies among health, education, and social protection.